Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jsfa.9956
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and bioactive properties of Cichorium spinosum L. in relation to nitrate/ammonium nitrogen ratio

Abstract: BACKGROUND Nitrogenous fertilizers may affect the yield and quality of leafy vegetables via the application rate and nitrogen form. In the present study, the effect of the nitrate:ammonium nitrogen ratio in the nutrient solution on the chemical composition and bioactive properties of Cichorium spinosum leaves was evaluated. For this purpose, C. spinosum plants were fertigated with nutrient solution containing different ratios of nitrate: ammonium nitrogen: (i) 100:0 NO3‐N:NH4‐N; (ii) 75:25 NO3‐N:NH4‐N; (iii) 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
6
24
1
Order By: Relevance
“…The highest individual and total organic acid contents were observed with the CFZ treatment (0.57 ± 0.01 g/kg fw), while the lowest values were recorded with the SR treatment (0.29 ± 0.04 g/kg fw). Similarly to in our study, Zhang et al [86] reported that increased nitrogen availability resulted in an increase in organic acid content in spinach, while the nitrogen source may also affect organic acid content in edible greens [87,88]. Moreover, the addition of zeolite seems to have a beneficial effect on organic acid accumulation, a finding that is probably associated with the better nitrogen availability in soil after zeolite application [41,89].…”
Section: Resultssupporting
confidence: 84%
“…The highest individual and total organic acid contents were observed with the CFZ treatment (0.57 ± 0.01 g/kg fw), while the lowest values were recorded with the SR treatment (0.29 ± 0.04 g/kg fw). Similarly to in our study, Zhang et al [86] reported that increased nitrogen availability resulted in an increase in organic acid content in spinach, while the nitrogen source may also affect organic acid content in edible greens [87,88]. Moreover, the addition of zeolite seems to have a beneficial effect on organic acid accumulation, a finding that is probably associated with the better nitrogen availability in soil after zeolite application [41,89].…”
Section: Resultssupporting
confidence: 84%
“…The higher oxalic acid content observed in the cultivated plants compared to the wild ones could be explained by differences in pH level, nitrogen availability, and/or nitrogen form available in the growing medium and natural soil, respectively. Lower levels of oxalic acid have been observed in Cichorium spinosum L. [66], purslane [67] and spinach [68] with an increasing proportion of NH 4 -N versus NO 3 -N, which is likely to be observed in a natural soil versus a cultivated and more aerated soil. Yet, the high level of oxalic acid observed in cultivated plants could also be explained by a higher availability of total nitrogen in the cultivation system compared to the non-fertilized wild plants.…”
Section: Organic Acids Compositionmentioning
confidence: 95%
“…The ability of wild species to resist or tolerate stressful conditions suggests they could be used as alternative farming options in soils and climates where conventional species are difficult or impractical to be grown; for the same reason, these species can become an option for small-scale farming allowing the farmers to be competitive within the rapidly changing global market and market needs for novel foods [5][6][7][8][9][10]. Until recently, many reports have highlighted the importance of growing conditions and cultivation practices for producing wild edible greens, focusing on the domestication of these species, their incorporation in sustainable cultivation systems and the rational use of natural resources [2,[11][12][13][14][15]. Moreover, several efforts have been made to emphasize the health benefits resulting from the inclusion of these species in modern diets, since they usually contain numerous bioactive secondary metabolites associated with positive health effects [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Disciglio et al [11], who studied the chemical composition of wild and cultivated Borago officinalis L., Cichorium intybus L. and Diplotaxis tenuifolia L. plants, reported higher contents of total phenols and antioxidant activity for wild C. intybus and B. officinalis plants, whereas no significant differences were reported in the case of D. tenuifolia. Moreover, cultivation practices such as the fertilization regime, the salinity level, the harvesting stage and the growing medium could affect the chemical composition and the overall quality and the bioactive properties of the final product [2,8,14,15,48,49].…”
Section: Introductionmentioning
confidence: 99%